Branching onsets and empty nuclei - Noam FAUST (Isogloss)
In the Croissant Romance variety of Saint-Pierre-le-Bost (SPLB), branching onsets can be split by epenthetic vowels. In addition, epenthetic vowels should be distinguished from weak, non-epenthetic ones, although both are identical in quality – because only the latter can be stressed. The consequences of these facts for autosegmental representations are explored in this paper. The splitting of branching onsets is claimed to argue in favor of a Strict CV view (Lowenstamm 1996, Scheer 2004). An account is proposed within this approach that involves a distinction between two types of featurally empty V-slots. Finally, a parameter is put forth regarding the realization of such V-slots which distinguishes French-type languages from SPLB-type languages.